LACK OF MORALITY IN THE GREAT GATSBY NOVEL - Muhammad Raka Iqbal Fadil Muharom; Nazelia Lestari Budiawan; Aghnia Awalliyah Salsabila; Radja Fatni Al Fazri; Nurholis (Cahaya Ilmu Bangsa Institute, 2025)
The aim of this paper is to analyze the lack of morality in F. Scott Fitzgerald's The Great Gatsby as seen from the social and economic context, the morals of the main characters, the theme of betrayal and disappointment, moral symbolism, and modern relevance. The social and economic context highlights the background of the Jazz Age and the American Dream and the impact of materialism on the behavior and values of society at that time. The morals of the main characters: Jay Gatsby, Daisy Buchanan, and Tom Buchanan are described in detail about their lack of morality. The theme of betrayal and disillusionment which is a common topic in the novel exposes the relationships between characters and moral betrayal, Gatsby's disillusionment with the idealism of love, and society's reaction to moral offences. Moral symbolism examines the symbol of Dr. T.J. Eckleburg's eyes as a representation of moral surveillance and the colors and visual elements depicting moral helplessness. Finally, modern relevance provides an overview of how the themes of morality in the novel are still relevant to modern society. The results of this analysis are presented to provide new insights into how the Jazz Age and the idea of the American Dream affect aspects of morality.